2017
DOI: 10.18632/oncotarget.20097
|View full text |Cite
|
Sign up to set email alerts
|

Pro-invasive properties of Snail1 are regulated by sumoylation in response to TGFβ stimulation in cancer

Abstract: Transforming growth factor β (TGFβ) is a key regulator of epithelial-to-mesenchymal transition (EMT) during embryogenesis and in tumors. The effect of TGFβ, on ΕΜΤ, is conveyed by induction of the pro-invasive transcription factor Snail1. In this study, we report that TGFβ stimulates Snail1 sumoylation in aggressive prostate, breast and lung cancer cells. Sumoylation of Snail1 lysine residue 234 confers its transcriptional activity, inducing the expression of classical EMT genes, as well as TGFβ receptor I (Tβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 55 publications
4
17
0
1
Order By: Relevance
“…Ectopic expression of a SUMO loss of function Snail in which Lysine 234 is converted to arginine was reported to reduce the ability of TGFβ to induce migration and invasion of prostate cancer cells as compared to wild-type Snail-expressing cells ( Figure 3 ). SUMOylation was suggested to promote c-Jun-Snail interaction and responsive-gene expression [ 60 ]. Further studies are required to identify the SUMO E3 ligase that promotes Snail SUMOylation to provide a possible target in suppressing TGFβ-induced EMT.…”
Section: Emt-tfs As Targets Of the Sumo Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Ectopic expression of a SUMO loss of function Snail in which Lysine 234 is converted to arginine was reported to reduce the ability of TGFβ to induce migration and invasion of prostate cancer cells as compared to wild-type Snail-expressing cells ( Figure 3 ). SUMOylation was suggested to promote c-Jun-Snail interaction and responsive-gene expression [ 60 ]. Further studies are required to identify the SUMO E3 ligase that promotes Snail SUMOylation to provide a possible target in suppressing TGFβ-induced EMT.…”
Section: Emt-tfs As Targets Of the Sumo Pathwaymentioning
confidence: 99%
“…Further studies are required to identify the SUMO E3 ligase that promotes Snail SUMOylation to provide a possible target in suppressing TGFβ-induced EMT. Interestingly, the TβRI-ICD retains the SUMO consensus lysine residue and which has been shown to be a target for SUMOylation [ 60 ]. Whether the SUMOylation of the TβRI alters its cleavage and subsequent activity with Snail remains to be investigated.…”
Section: Emt-tfs As Targets Of the Sumo Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, Snail expression is associated with resistance to chemotherapy, decreased survival, high recurrence rates, and poor prognoses (Suresh et al, 2016). In accordance with its profound role in development and diseases, the level of Snail protein is tightly regulated through various extracellular signaling including transcription or protein degradation (Park et al, 2010;Suresh et al, 2016;Gudey et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Snail is a labile protein with an estimated half-life of about 30 min (Park et al, 2010;. Several studies demonstrated that Snail can be quickly degraded via ubiquitinationmediated protein hydrolysis pathway (Suresh et al, 2016;Gudey et al, 2017). Several ring domain-containing E3 ligases, such as Fbxl5 (Wu et al, 2015), Fbxl14 (Vinas-Castells et al, 2010;Diaz and de Herreros, 2016), Fbxw1 (b-Trcp) (Vinas-Castells et al, 2014;Diaz and de Herreros, 2016), Fbxo11 (Zheng et al, 2014;Jin et al, 2015), and SCF-FbxO45 (Xu et al, 2015), have been identified to ubiquitinate Snail and promote its degradation in various cell types.…”
Section: Introductionmentioning
confidence: 99%